Common property resource degradation and tribal livelihood - Sahoo, Raghunath (New Delhi : SSDN Publishers & Distributors, 2018)
Study conducted in Keonjhar District, Odisha, India.
Includes bibliographical references and index.
Keywords: LAND DEGRADATION; COMMON PROPERTY RESOURCE